KREATIVITAS GURU DALAM MENGGUNAKAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN FIQIH KELAS VII DI MTSS FASTABIQUL KHAIRAT GUNUNG MALINTANG KAB. LIMA PULUH KOTA - Febriani Uswa Hasanah; Charles Charles; Zulfani Sesmiarni; Supratman Zakir (Jurnal Bintang Pendidikan Indonesia, 2023)
The background of this research is based on the results of observations with teachers and students that teachers in using audio-visual-based learning media are already creative but not maximally. From the teacher's perception, stated that they were still clueless in using IT-based media. With creativity, it is hoped that the implementation of learning will run effectively, be fun, and lead to threats to the expected quality of learning. The solution taken by the teacher is to learn more about technology, and diligently attend training. The goal to be achieved in this research is to find out the form of teacher creativity in using audio-visual media in class VII fiqh subjects at MTsS Fastabiqul Khairat Gunung Malintang. This type of research is descriptive qualitative research which is a form of the most basic research, aimed at describing or describing phenomena that exist or occur in the field. In this study the authors describe Teacher Creativity in Using Audio Visual Media in Jurisprudence Subjects at MTsS Fastabiqul Khairat Gunung Malintang. The technique of collecting data in this research is through interviews, where researchers ask for answers by way of debriefing verbally with research informants. Based on the results of the research conducted by the authors, it was found that teachers at MTsS Fastabiqul Khairat Gunung Malintang have not been optimally able to be creative in using audio-visual media seen from the four indicators of creativity. First, the smoothness of the teacher, namely being able to adapt material to the media but the teacher has difficulty mastering sources from the internet, secondly, in terms of flexibility, namely the teacher uses applications but has not been fully able to use the application fluently, the third is teacher creativity in terms of elaboration, namely the teacher adding information in the media, fourth, teacher creativity in terms of originality, that is, teachers can use audio-visual media in their classes.